Early skin colonization by Staphylococcus epidermidis and Staphylococcus aureus reveals environment-dependent synergistic effects - Ngari, Chrisse; Poulet, Valérie; Percoco, Giuseppe; Peno-Mazzarino, Laurent; Seyer, Damien (Frontiers in Microbiology, 2025)
IntroductionThe skin microbiome is crucial for skin health and homeostasis. It contributes to immune defense, promotes epidermal differentiation, and supports a robust skin barrier function. Despite its importance, few studies have used model skin systems to examine how simple bacterial communities interact and how they impact the skin.MethodsWe studied the interaction between a skin commensal, Staphylococcus epidermidis, and a pathogen, Staphylococcus aureus, by performing inoculations and co-inoculations on Reconstructed Human Epidermis (RHE) models maintained under classical humid conditions (>90% relative humidity) or dry conditions (<25% RH). In parallel, inoculations were conducted on human skin explants using a novel culture setup preserving physiological humidity levels (40–60% RH). Bacterial attachment was assessed 4 h post-inoculation. At 24 h, histology was examined, three natural moisturizing factors (NMFs) were quantified. Filaggrin (FLG) and ceramide levels were analyzed to assess the skin barrier function.ResultsIn contrast to previous findings at 24 h, co-inoculation increased S. epidermidis and S. aureus attachment in RHEs, but only under humid conditions. Only RHE maintained in dry conditions and skin explant revealed an effect of co-inoculation on filaggrin (FLG), yet an increase in RHEs and a decrease in skin explants. In both RHEs maintained in dry conditions and skin explants, NMF levels were consistently reduced following co-inoculation. In RHEs and skin explants, inoculation with S. aureus alone also lowered NMFs, with co-inoculation further amplifying this effect. Finally, ceramide levels increased similarly across both inoculations and co-inoculation.DiscussionRevealing unexpected early interactions between S. epidermidis, S. aureus, and the skin, our results could suggest that co-inoculation may trigger a synergetic disruption of the barrier function. Alternatively, it could imply that co-inoculation might reinforce the epidermal barrier via a S. aureus-mediated stimulation of the protective functions of S. epidermidis. Further studies are needed to confirm these effects and determine whether they are strain-specific or more broadly applicable.